MySpace for musicians - Vincent, Fran (Thomson Course Technology, 2007)
MySpace is one of the most popular websites on the Internet today, with millions of pages of user-generated content. This makes MySpace an ideal tool for musicians interested in promoting their music to the widest possible audience. Many acts have gone from the garage to a recording contract by using MySpace as their launching pad. MySpace for Musicians is for every band, soloist, side musician, record label, publisher, music manager, and entertainment-affiliated company who wants to use MySpace to its fullest potential. It teaches musicians how to design a MySpace page optimized for music promotion and distribution and how to best use MySpace to effectively market music. It includes expert advice on how to market oneself to the MySpace community and how to best position and advertise MySpace pages in the real world. The book caters to musicians who are unfamiliar with the network, as well as musicians who already have a MySpace page but who want to learn how to make better use of it. This is the most comprehensive book on how musicians can maximize the most popular and successful band promotion site